Law Enforcement And The Important Role Of Communities In Preserving Mangrove Forests In Protecting The Environment - Muhammad Irfan Faisal Barus; Selfi Helfianto Simarmata; Aulia Perbina Br Tarigan; Suci Ramadani (International Journal of Society and Law, 2024)
Mangrove forest conservation requires integrated efforts between law enforcement and community participation. This study analyzes the extent to which law enforcement and community roles contribute to maintaining the sustainability of mangrove forests. The results of the study indicate that strict law enforcement can provide a deterrent effect for perpetrators of violations and create a conducive climate for conservation efforts. On the other hand, community participation in conservation activities can increase the success of conservation efforts and strengthen a sense of ownership of mangrove forests. This study concludes that synergy between law enforcement and community participation is the key to success in maintaining the sustainability of mangrove forests and protecting the environment.